Comparative Study of Diets of Mixed-species-zooplankton and Formulated-feed Effects on Physicochemical Parameters, Growth and Survival Rate of Clarias gariepinus Larvae - Obhahie, Austeen Obhahie (Iraqi Journal of Aquaculture, 2025)
Comparative analysis of live-mixed-species-zooplankton-diet (LMSZD) and formulated-feed-diet (FFD) effects on culture-media physicochemical parameters, growth and survival rate of Clarias gariepinus larvae were assessed for 15 days. The experiment was conducted in six plastic-aquaria (30 liters) in triplicates, designated as Tanks-A and Tanks-B. Each tank was stocked with 200 individuals 3-days old post-yolk larvae of initial mean-weight and mean-length of 0.0128 g and 0.65 cm respectively. Live-zooplankton-fed-larvae (LZFL) were placed in Tanks-A, while formulated-feed-fed-larvae (FFFL) were in Tanks-B. The larvae were fed twice daily at ad-libitum. Physicochemical parameters analysis was done at two days interval. The cumulative-mean-values recorded in Tanks-A and Tanks-B respectively were; temperature (24.24; 23.88 °C), pH (7.29; 6.96), electrical-conductivity (263.84; 276.7 µs/cm); total-alkalinity (74.99; 93.45 ppm), total-dissolved-solids (127.79; 138.8 ppm), dissolved-oxygen (7.02; 5.08 ppm), biological-oxygen-demand (1.08; 1.77 ppm) and free-carbon-dioxide (239.14; 11.08 ppm). The growth parameters for LZFL and FFFL respectively were length increment (1.20; 1.00 cm), weight gain (0.1755; 0.1456 g) and specific growth rate [SGR] (%) were 17.92; 16.78. The survival rates (%) were 89.50; 55.00, while the Condition Factor [K] (%) were 2.77; 3.53 for LZFL and FFFL respectively. BOD, Temperature, pH, and CO2 did not have significant difference (P>0.05). EC, TA, TDS, and DO values exhibited significant differences at (P≤0.05). Growth parameters mean exhibited a gradual daily upsurge in both treatments. LZFL maintained a higher mean values than FFFL, through the experiments. Both LZFL and FFFL growth indices values exhibited significant difference (P≤0.05).